Synthesis, Characterization, and Catalytic Activities of A Nickel(II) Monoamido‐Tetradentate Complex: Evidence For NiIII–Oxo and NiIV–Oxo Species. Issue 13 (3rd February 2017) - Bok, Kwon Hee; Lee, Myoung Mi; You, Ga Rim; Ahn, Hye Mi; Ryu, Ka Young; Kim, Sung‐Jin; Kim, Youngmee; Kim, Cheal
Abstract: A new mononuclear nickel(II) complex, [Ni II (dpaq)Cl] (1 ), containing a tetradentate monoamido ligand, dpaq (dpaq=2‐[bis(pyridin‐2‐ylmethyl)amino]‐ N ‐(quinolin‐8‐yl)acetamide), has been synthesized and characterized by IR spectroscopy, elemental analysis, and UV/Vis spectroscopy. The structure of the nickel complex has been determined by X‐ray crystallography. This nonheme Ni II complex1 catalyzed the epoxidation reaction of a wide range of olefins with meta ‐chloroperoxybenzoic acid ( m ‐CPBA) under mild conditions. Olefin epoxidation using this catalytic system has been proposed to involve a new reactive Ni IV –oxo (4 ) species, based on the evidence from a PPAA (peroxyphenylacetic acid) probe, Hammett studies, H2 18 O exchange experiments, and ESI mass spectroscopic analysis. Moreover, the nature of solvent significantly influenced partitioning between heterolytic and homolytic O−O bond cleavage of the Ni–acylperoxo intermediate (2 ). The O−O bond of2 proceeded predominantly through heterolytic cleavage in a protic solvent, such as CH3 OH. These results suggest that possibly a Ni IV –oxo species is a common reactive intermediate in protic solvents. The two active oxidants, namely Ni IV –oxo (3 ) and Ni III –oxo (4 ), which are responsible for stereospecific olefin epoxidation and radical‐type oxidations, respectively, operate in aprotic solvents. Abstract : Ni IV ‐oxo versus Ni III ‐oxo : A new mononuclear nickel(II) complex [Ni II (dpaq)Cl] (dpaq=2‐[bis(pyridin‐2‐ylmethyl)amino]‐ N ‐(quinolin‐8‐yl)acetamide) displayed efficient catalytic activity toward numerous olefin epoxidation reactions. Partitioning between the heterolytic and homolytic O−O bond cleavage of the Ni–acylperoxo intermediate was significantly affected by the nature of the solvent. An Ni IV –oxo species was the common reactive intermediate in protic solvents, whereas the two active oxidants, Ni IV –oxo and Ni III –oxo, operated in aprotic solvents.